Design characteristics, codes and standards of natural fibre composites - Alam M.A.; Sapuan S.M.; Mansor M.R. (Elsevier Inc., 2023)
Availability; Codes (standards); Concrete beams and girders; Construction; Construction industry; Design; Environmental management; Fiber reinforced plastics; Greenhouse gases; Natural fibers; Reinforced concrete; Sustainable development; Building and construction; Environmental performance; Fibre reinforced polymers; Natural fibre composites; Reinforced concrete beams; Research and application; Shear strengthening; Sustainable construction; Structural design